The Metabolic and Reproductive Effect of Exercise and Diet in Obese PCOS Women : Let the Evidence Guide Us - Fadhilah, Annisa Farah; Wicaksono, R. Bagas; Nurnadziah, F. (Asian Journal of Health and Applied Sciences, 2023)
One of the most strongly related reproductive diseases in obese women is a polycystic ovarian syndrome. PCOS also suffer other comorbidities, such as insulin resistance. This review focus on identifying the metabolic and reproductive effect of diet and exercise in obese PCOS women. We searched for articles published from January 2004 to February 2022 and used electronic databases. We used the purposive sampling method then these articles were selected by inclusion and exclusion criteria. Lifestyle modification programs with an emphasis dietary and exercise interventions have been successful in reducing the risk of comorbidities in the general population and improving reproductive and metabolic features in PCOS. Lifestyle modification should be incorporated in treating obese PCOS patients to reduce their long-term risks for diabetes, hypertension, dyslipidemia, and cardiovascular disease and to increase the probability of spontaneous pregnancy. However, the specific guideline for lifestyle modification emphazising in diet and exercise for PCOS patients requires the large size of clinical trial research to find the best type of interventions in lifestyle modifications with the same outcome parameters.